MENINGKATKAN KEMAMPUAN BERBAHASA ANAK MELALUI BIMBINGAN KONSELING TEKNIK PLAY TERAPI DI TK KARUNIA KECAMATAN MEDAN JOHOR T.A. 2014/2015 - Nasrun, Nasrun; Harahap, Melianni (JURNAL DIVERSITA, 2015)
This study aimed to help the children with language problems by using play therapy which are integrated in learning activities in kindergarten Karunia T.A 2014/2015. This research was a classroom action research (PTK), which consists of the second cycle, that cycle I and cycle II. The population is all kindergarten students and the sample are 46 kindergarten students who are having language development problems. The data collection technique was observation. Based on data analysis that the children with language development problem in the first cycle there are three children (50%) who had experienced the development of language with an average of 61.6 and there were three children (50%) who are not experiencing language development. Thus it can be seen that a childs ability to follow the play therapy is still relatively unfavorable within 5 children. In the second cycle as much as 5 children (83.3%) who had experienced the development of language and only 1 child (16.6%) were still not good who have not experienced the development of language, with the class average value is 84.1. Based on these results it can be concluded that the counseling play therapy techniques may improve childrens language development in kindergarten Karunia Medan Johor.Keyword: Counseling, language Development, Play Therapy